A relação da digital influencer e o youtube: o caso do Magazine Luiza. - Bezerra, Artur Henrique Araújo (2021)
This Research introduce a study regarding digital marketing and its strategies directed to a digital platform on Youtube. The focus of the study is the Magazine Luiza case and her character, Magalu, the company's digital influencer. Many aspects related to the shift from traditional marketing to digital marketing are necessary for reflection in order to understand the real transformations that are taking place in the digital transformation scenario. In addition, the Research covers the evolution of marketing, bringing aspects and characteristics that have led to evolution up to the present moment, as well as valu-ing the study's understanding of what digital platforms are like. Finally, It is presented regarding the AIDA methodology and how it impacts the strategies of the videos of the character Magalu on his Youtube channel.